Fostering resilience of drug dependents through cognitive behavior therapy - Soliven, Raoul R. (College of Education, University of the Philippines Diliman, 2018)
The purpose of the study were to (1) examine the efforts of drug dependents towards recovery and (2) evaluate the effectiveness of CBT in fostering resiliency among drug dependents. Using an Embedded Mixed Method Design, nine self-confessed Tokhang drug surrenderres, whose ranges from 30-52- years old, were involved in the study for nine weeks, with one hours CBT counselling session per participant for each week. The Personal Data Sheet, Drug Avoidance Self-Efficacy Scale (DASES) and BASIC ID Guide were used as assessment tools in assessing and/or evaluating the (1) demographic profile of participants, (2) resiliency level of participants when it comes to drug avoidance, and (3) resiliency concerns of participants, respectively, before and after intervention. Results showed that CBT is effective in fostering resiliency for change and recovery of drug dependents. It allowed them to reframe their thoughts, feelings and actions, and helped them develop coping skills. In addition, CBT is seen to be a promising counselling framework compatible with drug intervention programs for drug dependents. Finally, implication to counselling practice, government interventions for drug surrenderres, and policy making were discussed.